When crowds play god: a Promethean perspective on crowdfunding. Issue 2 (4th March 2022) - Conboy, Kieran; Gleasure, Rob; Morgan, Lorraine
ABSTRACT: Crowdfunding projects have been the subject of contrasting narratives. To many, they are the antithesis of predatory bottom-line business ventures, and to others, they are an under-regulated vehicle for immature, or unscrupulous project owners to exploit inexperienced and vulnerable investors. These differences are significant, given many use crowdfunding to build public awareness and project a positive image. We use the myth of Prometheus – the Greek god associated with "defiant progress" and technological advancement – as a sensitising lens to build a set of competing, dialectic archetypes. We then apply these archetypes through a Hegelian dialectic analysis of three high-profile crowdfunding campaigns. The overarching contribution of the study is that it provides a foundation for discussion of the positive and negative narratives surrounding crowdfunded project owners and explicates the limitations of crowdfunding as an enabler of positive systemic change. The dialectic approach provides a systematic means of identifying the essence of disagreement between narratives. While it may be too early to predict the outcomes for emerging technology-driven initiatives such as crowdfunding, the use of myth offers a sophisticated means to look for "rhyming" phenomena, where the phenomena at play are similar to the grand frailties of humankind throughout history.